Laboratory to Clinical Investigation of Carbapenem Resistant Acinetobacter baumannii Outbreak in a General Hospital - Guo-xin, Mo (Kowsar, 2014)
BACKGROUND: The number of reported cases, infected with carbepenem resistant Acinetobacter baumannii (CRAb) and multi-drug resistant (MDR) Acinetobacter species had gradually increased in most PLA general hospital wards from April to June in 2007. OBJECTIVES: We have described the investigation of an outbreak of CRAb and MDR Acinetobacter in PLA general hospital, Beijing. The prospective and retrospective findings were identified and analyzed to study the infection causes. MATERIALS AND METHODS: A. baumannii samples were collected from the patients and environment in each hospital unit. The onset times were recorded according to their case information. All samples were characterized by genotype and compared using pulsed-field gel electrophoresis (PFGE). The microorganism susceptibility was tested using the in vitro minimal inhibitory concentration (MIC) breakpoints method. RESULTS: A total of 69 A. baumannii strains were successfully isolated from 53 patients. About 89.1% of them were resistant to ampicillin and 89.2% to cefotaxime and 75.4% to all standard antibiotics. PFGE analysis revealed that nine of the isolates had unique clones and the epidemic clone types were A, B and C. CONCLUSIONS: The A. baumannii outbreak, was caused by MDR A. baumannii. The strains had widely spread among 12 departments especially in surgical intensive care unit (SICU), emergency intensive care unit (EICU) and the department of respiratory disease. The outbreak was more likely caused by the A. baumannii infected or carrier patients and EICU was its origin.